2012
DOI: 10.1080/09291016.2011.630183
|View full text |Cite
|
Sign up to set email alerts
|

Are educational interventions able to prevent excessive daytime sleepiness in adolescents?

Abstract: This study evaluated the effect of an educational sleep program (ESP) on adolescent sleep patterns and daytime sleepiness. Twenty-one adolescents (13-14 years old) participated in the study. Two groups were formed: experimental (n ¼ 10), subjected to the educational program for sleep (EPS); and Control (n ¼ 11), not subjected to the EPS. Sleep/wake cycle (SWC) data were recorded with actigraphy; subjective sleepiness levels and psychomotor performance were assessed before and after the ESP. The data on sleep p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
“…Although some sleep education studies have specifi cally targeted problematic sleepers, [16][17][18][19] most have delivered broad based general sleep education programs using a preventative model. [20][21][22][23][24][25][26][27][28] School based health education programs such as those targeting physical activity and/or diet are common and effi cacious. 29 However, sleep education is in its infancy.…”
Section: Lessons Learned From Sleep Education In Schools: a Review Ofmentioning
confidence: 99%
See 3 more Smart Citations